Deconstructing comparative sport policy analysis: assumptions, challenges, and new directions. Issue 4 (2nd October 2018) - Dowling, Mathew; Brown, Phil; Legg, David; Grix, Jonathan
ABSTRACT: Despite progress within comparative sport policy analysis over the past two decades and advancements within the broader comparative sociology literature, comparative analysis within sport policy/management remains limited and challenging. Furthermore, there is a dearth of literature that explicitly addresses the philosophical, methodological, and practical challenges of comparing sporting nations. We address this shortcoming by developing a framework to interrogate the philosophical assumptions and methodological approaches of comparing sporting nations. In doing so, we review the current state of comparative sport policy research and elaborate on the challenges and limitations of conducting comparative sport policy analysis. Thus, we seek to deconstruct the theory and method of comparative sport policy research by exploring its underlying assumptions and challenges. Ultimately, our broader intention is to reengage and reinvigorate scholarly debate surrounding the philosophical and methodological approaches of comparing sporting nations.